PENGARUH FAKTOR PERSONAL DAN FAKTOR LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA STIA BNM PARIAMAN - Dorris Yadewani (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The study of STIA BNM Pariamna students aims to examine the impact of personal factors on entrepreneurial interests, the impact of family factors on entrepreneurial interests, and the impact of personal and family factors on enterprise interests. In this study, the population is STIA BNM Pariaman students, while the sample is STIA BNM Paraman students who are active in the 2022-2023 general school of state administration by semester level, age, and gender. This study employs quantitative descriptive methods and an ex post facto research design. Online questionnaires were distributed to sample members to collect data. Techniques for Data Analysis Using the SPSS 26 Software This study discovered: 1) 1) At STIA BNM Pariaman, personal factors have a significant influence on entrepreneurial students' interests. 2) There is a significant relationship between family environmental factors and entrepreneurial students' interest at STIA BNM Pariaman. 3) Personal and family environmental factors have a significant influence on entrepreneurial students' interests at STIA BNM Pariaman